Iron and Nickel Phthalocyanine-Modified Nanocarbon Materials as Cathode Catalysts for Anion-Exchange Membrane Fuel Cells and Zinc-Air Batteries** - Zagal-Moya, J; Zagal-Moya, J (John Wiley and Sons Inc, 2022)
Iron and nickel phthalocyanines along with different carbon supports, i. e., multi-walled carbon nanotubes (MWCNT), graphene, carbide-derived carbon, Vulcan carbon, and mesoporous carbon (MC, from Pajarito Powder, LLC), are used to prepare six bimetallic (Fe, Ni) N-doped carbon-based catalysts. The aim of this work is to investigate the electrocatalytic activity of bimetal phthalocyanine-modified nanocarbon catalysts, e. g., the effect of carbon supports on the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER), including the anion-exchange membrane fuel cell (AEMFC) and rechargeable zinc-air battery (RZAB) configuration. The catalysts exhibit excellent electrocatalytic activity as exemplified by their half-wave potential (E1/2) for ORR and the potential at which the OER current density reaches 10 mA cm−2 (Ej=10), but the best performing catalysts are FeNiN−MC (E1/2=0.88 V, Ej=10=1.58 V) and FeNiN−MWCNT (E1/2=0.87 V, Ej=10=1.59 V). In AEMFC analyses, FeNiN−MWCNT cathode provides peak power density (Pmax) of 406 mW cm−2, slightly higher than that of FeNiN−MC (Pmax=386 mW cm−2). Both catalysts exhibit a good RZAB performance (Pmax of 85 mW cm−2 for FeNiN−MWCNT). The assembled RZABs run stably for 48 h without any significant loss of performance. © 2022 Wiley-VCH GmbH.